2009
DOI: 10.1113/jphysiol.2009.176040
|View full text |Cite
|
Sign up to set email alerts
|

Human cutaneous C fibres activated by cooling, heating and menthol

Abstract: Differential A-fibre block of human peripheral nerves changes the sensation evoked by innocuous cooling (∼24• C) of the skin from 'cold' to 'hot' or 'burning', and this has been attributed to activity in unidentified unmyelinated fibres that is normally masked or inhibited by activity in Aδ cold fibres. Application of the TRPM8 agonist menthol to the skin evokes 'burning/stinging' as well as 'cold', and the unpleasant sensations are also enhanced by A-fibre block. In this study we used microneurography to sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 53 publications
(90 reference statements)
2
118
0
3
Order By: Relevance
“…Previous work indicated several alternative neurophysiological mechanisms and pathways, including the difference in activity between cold‐specific and polymodal nociceptive neurons at the thalamocortical level,7, 11 summation by wide dynamic range neurons in the deep dorsal horn4, 6 and type 2 C‐afferents 36. More specifically, animal work suggests reciprocal cross‐inhibition between cold and warm afferents in the spinal cord 37, 38.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work indicated several alternative neurophysiological mechanisms and pathways, including the difference in activity between cold‐specific and polymodal nociceptive neurons at the thalamocortical level,7, 11 summation by wide dynamic range neurons in the deep dorsal horn4, 6 and type 2 C‐afferents 36. More specifically, animal work suggests reciprocal cross‐inhibition between cold and warm afferents in the spinal cord 37, 38.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies have provided the basis for well-established notions, such as fibers specificity in humans (i.e. the class of specific nerve fibers which are involved in warm and cold temperatures detection), recent evidence based on microneurographic recordings of activity in primary thermo-sensory nerve fibers in awake humans has challenged some of these well-established ideas (39,40,264).…”
Section: Neurophysiology Of Temperature Sensationmentioning
confidence: 99%
“…cat) (145,148,162) and primates (e.g. macaque) (74,147,162,165,166,174,201) animal models as well as in humans (39,40,107,146,151,165,166,184,309). From a neuroanatomical point of view, studies in primates have shown that cold-sensitive fibers appear to belong primarily to the Aδ range, i.e.…”
Section: Peripheral Thermo-receptive Nerve Fibersmentioning
confidence: 99%
See 2 more Smart Citations